(untitled) (KYAMC Journal, 2017)
Lung hydatid cyst may be primary or secondary. In our case, the cyst was a single one locating in right middle lobe. Hydatidosis locating in different sites, particularly the liver may be associated. Initial growth of primary hydatidosis is asymptomatic. The evolution of the cyst may produce bronchial fistulization and intrapleural rupture. Breaking of primary visceral hydatid cyst in a vein or heart producing hydatidosis is rare. Progressive respiratory deficiency and right ventricular failure due to multiple malignant primary hydatidosis is a special form. The recognition of certain details of the lesion and discoverothers are not visible by conventional radiography, can be done by ultrasonography, computed tomography and magnetic resistance imaging. Surgery is the treatment of choice. Chemotherapy is used in general as a complement to surgical treatment to prevent recurrence. The goal of surgery is to remove the parasite and to treat the bronchialpericyst pathology with other associated lesions. The results are now commonly satisfactory. Prolonged air leakage and pleural infection are most frequent complication. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 427-430